Corrigendum: “Corrigendum to ‘Multiple myeloma: EHA-ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up’”: (Annals of Oncology (2022) 33(1) (117), (S0923753421044999), (10.1016/j.annonc.2021.10.001)) - Dimopoulos, M. A.; Moreau, P.; Terpos, E.; Mateos, M. V.; Zweegman, S.; Cook, G.; Delforge, M.; Hajek, Roman; Schjesvold, F.; Cavo, Michele; Goldschmidt, Hartmut; Facon, T.; et al. (Annals of Oncology, 2022)
The authors regret that affiliations for Dr Michele Cavo were published incorrectly in the original paper. Please refer to the updated affiliations above. The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2023-03-23